Celeridad en los trámites de beneficios penitenciarios a favor de las mujeres privadas de la libertad, por parte de los jueces de garantías penitenciarias. - Guerrero Veliz, Génesis Ivonne (2022)
This degree thesis entitled "Speed in the procedures for prison benefits in favor of women deprived of their liberty, by judges of prison guarantees", arises from the need to conduct a study on requests for access to a semi-open regime presented by women deprived of their liberty who are not attended to promptly by the judges of penitentiary guarantees, which affects their constitutionally guaranteed rights, such as access to prompt and timely justice. The study carried out shows that the lack of a reasonable term established in the law for the requests for access to a semi-open regime to be resolved by the judges of penitentiary guarantees violates the constitutionally guaranteed principle of speed, which affects the violation of not only the principle of speed but also other rights that are guaranteed to persons deprived of liberty, with women deprived of liberty being the prison population most affected due to their greater degree of vulnerability. The purpose of the research is to find an optimal and viable solution, which allows safeguarding the rights of women deprived of liberty, as well as their effective access to prison benefits and therefore to a satisfactory social rehabilitation, through a perspective of gender. The inductive, deductive, comparative, and analytical method was used, which allowed the elaboration of the conceptual, doctrinal, and legal part; In addition, interviews and surveys were conducted with legal professionals, the results of which served to propose the project of legal reform to the Comprehensive Criminal Organic Code, to incorporate within article 670, a reasonable term for the judges of penitentiary guarantees to resolve the requests. submitted by women deprived of liberty to access the semi-open regime